The Dilemma of the Energy Law and Policy Triangle in Recent Energy Laws and Policies in Bangladesh - Sourav, Raisul Islam (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
The energy law and policy triangle are a complex area where energy law and policy are situated at the centre of a triangle and three other inalienable horns relating to this i.e. energy supply and energy security, cost relating to production of energy and environmental protection and preservation equally pull energy law and policy towards their direction. However, the energy law and policy emerge as a concern all over the world and states are taking initiative to ensure a balance among these three dilemmas. It is the reality that Bangladesh suffers severe shortage in power generation which also affects its overall economic development. Hence, in one hand, it needs to ensure continuous energy supply which is closely connected with country’s energy security also. On the other hand, it also needs to make a balance between the challenges of producing energy in affordable cost which will not adversely affect the environment as well. Nevertheless, Bangladesh, being a lower-middle income country at least put focus on the energy law and policy triangle in recent years. Still ensuring balance among these three opposite directions is still a challenge for Bangladesh. Despite that, the recent laws and policies relating to energy in Bangladesh show its commitment towards climate change mitigation which encourages more production and use of renewable energies in the country. Although there are some deficiencies in those laws and policies which can be overcome by further initiative. The State can reaffirm its position towards environmentally friendly affordable energy by amending those policies and legislations. This research paper is aimed to assess the dilemma of the Energy Law and Policy Triangle in recently legislated energy related laws and policies in Bangladesh. HYDRO Nepal Journal Journal of Water Energy and Environment Issue No: 22 Page: 10-15 Uploaded date: January 14, 2018